Identification and location of faults in electric power distribution systems from measurements and data on Gis platforms - Di Mauro, Guillermo Fabián (2018)
This paper presents the development of a collaborative computer tool for the location of faults in electricity distribution systems oriented to overhead lines. The methodology implemented for the location of the fault is based on the analysis of the fault impedance from the voltage and current data measured in the header of the damaged distributor and in the evaluation of all its branches. The results provided by the tool are displayed on the layout of the network in the environment of a Geographic Information System (GIS). The calculation algorithms developed use the topological and constructive information of the network that is stored in standardized files according to the requirements of State Control Organisms (Argentina). The tool was tested by modeling a distributor belonging to an electric power cooperative in a simulation program of power systems. The results of the implemented method showed maximum errors of the order of 5% in the actual location distance of the fault. The presentation of the results in the graphic environment of the network offers the operators a quick interpretation of the possible location of the fault, which results in a reduction of the repair times.